A high-adhesion printing ink and printing process thereof

By modifying the water-based polyurethane linker, vinyl fluoropolysiloxane is synthesized and polyol monomer is introduced, the problems of poor adhesion performance and poor water resistance of water-based polyurethane ink on low-surface energy substrates are solved, and printing inks with high adhesion and water resistance are achieved.

CN119101398BActive Publication Date: 2025-03-11CHANGZHOU ZHENGWEN PRINTING CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411217002.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-02
Publication Date
2025-03-11
Estimated Expiration
2044-09-02

AI Technical Summary

Technical Problem

The poor adhesion performance of water-based polyurethane ink connecting materials on low-surface energy substrates and poor water resistance, limiting their application range.

Method used

By modifying the aqueous polyurethane linker, vinyl fluoropolysiloxane, methyl trifluoropropyl cyclotrisiloxane and tetramethyltetraenyl cyclotetrasiloxane were used to synthesize vinyl fluoropolysiloxane, and polyol monomer was introduced through the thiol click reaction to improve the hydrophobicity and crosslinking density of the polyurethane.

Benefits of technology

It significantly improves the adhesion performance of printing ink on low-surface energy substrates and improves its water resistance, making it suitable for a wide range of printing applications.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to the technical field of inks, and in particular to a high-adhesion printing ink and a printing process thereof. In this scheme, polyurethane is used as a connecting material, and components such as polyurethane emulsion, isopropyl alcohol, and color paste are mixed and stirred evenly to obtain printing ink. The introduction of polyol monomers and chain extenders in the scheme can not only improve the adhesion of the ink to a PET substrate, but also improve the cross-linking density of polyurethane, thereby improving the water resistance of the printing ink. The printing ink can adapt to printing substrates with low surface energy, improve the adhesion performance of the printing ink on the substrate, and the printing ink has relatively excellent water resistance and excellent comprehensive performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of inks, in particular to a high-adhesion printing ink and a printing process thereof. Background Art

[0002] As an important water-based ink binder with excellent comprehensive performance, water-based polyurethane has great development and application prospects in printing fields such as food packaging plastic films. However, due to the limitations of its own composition and structure, water-based polyurethane ink binders have poor water resistance and poor adhesion performance on low surface energy substrates such as plastics, which greatly limits its application.

[0003] In response to this situation, the present application discloses a high-adhesion printing ink and a printing process thereof, by modifying the water-based polyurethane binder to improve the adhesion performance of the ink on low surface energy substrates, which is also one of the technical problems that technical personnel in this field urgently need to solve. Summary of the invention

[0004] The object of the present invention is to provide a high-adhesion printing ink and a printing process thereof to solve the problems raised in the prior art.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] A method for preparing a high-adhesion printing ink comprises the following steps:

[0007] Step (1): octamethylcyclotetrasiloxane, methyltrifluoropropylcyclotrisiloxane and tetramethyltetraenylcyclotetrasiloxane are mixed, stirred at 80-90° C. until uniform, then heated to 100-110° C., tetramethylammonium hydroxide aqueous solution and deionized water are added, and the mixture is kept warm for 2-3 hours, and the reaction is continued at 140-150° C. for 1-2 hours, and distilled under reduced pressure to obtain vinyl fluorine-containing polysiloxane;

[0008] Step (2): 4-methylallyl-1,2-benzenediol and thiol are mixed, an initiator is added, and the mixture is reacted under ultraviolet light for 2 to 3 hours to obtain a chain extender;

[0009] The vinyl fluorinated polysiloxane and the thiol are mixed, an initiator is added, and the mixture is reacted under ultraviolet light for 2 to 3 hours to obtain a polyol monomer;

[0010] Step (3): polypropylene glycol, dimethylol propionic acid and polyol monomer are mixed, stirred at 80-85° C. for 20-30 min, isophorone diisocyanate and dibutyltin dilaurate are added, the reaction is kept warm for 1-2 h, the temperature is lowered to 60-70° C., 1,4-butanediol and a chain extender are added, the reaction is kept warm for 2-3 h, the temperature is lowered to 40-50° C., acetone is used to reduce the viscosity, triethylamine is used for neutralization for 20-30 min, and deionized water is added for dispersion to obtain a polyurethane emulsion;

[0011] Step (4): Mix the polyurethane emulsion, isopropyl alcohol, color paste and deionized water, stir evenly, and obtain printing ink.

[0012] In a more optimized scheme, in step (2), the thiol is 2-mercaptoethanol and / or 3-mercapto-1,2-propylene glycol; the molar ratio of the thiol to 4-methylallyl-1,2-benzenediol is 1:(1-1.1); and the molar ratio of the vinyl group of the vinyl fluorinated polysiloxane to the thiol group is 1:(1-1.2).

[0013] In a more optimized solution, in step (2), the amount of the initiator used is 1 to 1.5 wt% of the total mass of the reactants; the initiator is any one of benzoin ethyl ether, benzoin dimethyl ether, and 1-hydroxycyclohexyl phenyl ketone.

[0014] In a more optimized scheme, in step (1), the mass ratio of octamethylcyclotetrasiloxane, methyltrifluoropropylcyclotrisiloxane and tetramethyltetraenylcyclotetrasiloxane is 1:(2-2.5):(1-1.2); the molar concentration of the tetramethylammonium hydroxide aqueous solution is 25%, and the amount used is 0.01-0.015wt% of the total mass of the reactants; and the amount of deionized water used is 0.05-0.08wt% of the total mass of the reactants.

[0015] In a more optimized scheme, in step (2), the preparation steps of 4-methylallyl-1,2-benzenediol are:

[0016] Dissolve catechol in dimethylformamide, add potassium carbonate and methyl chloropropene, stir and react at 65-75°C for 8-10 hours, separate and purify to obtain 2-(oxy-methylallyl)phenol; dissolve 2-(oxy-methylallyl)phenol in N,N-diethylaniline, heat to 180-190°C, react for 3-4 hours, separate and purify to obtain 4-methylallyl-1,2-benzenediol.

[0017] In a more optimized solution, the molar ratio of catechol to methyl chloropropene is (1.2-1.5):1; the molar ratio of catechol to potassium carbonate is 1:(0.6-0.7).

[0018] In a more optimized solution, in step (3), the amounts of the components used, in parts by mass, include: 25-30 parts of polypropylene glycol, 2-4 parts of dimethylol propionic acid, 6-8 parts of polyol monomer, 10-15 parts of isophorone diisocyanate, 0.3-0.5 parts of dibutyltin dilaurate, 2-4 parts of 1,4-butanediol, and 3-5 parts of chain extender; the solid content of the polyurethane emulsion is 30-40%.

[0019] In a more optimized solution, in step (4), the mass ratio of the polyurethane emulsion, isopropyl alcohol, color paste and deionized water is 6:1:1:3.

[0020] A more optimized solution is a high-adhesion printing ink prepared according to any of the preparation methods described above.

[0021] A more optimized solution is an ink printing process, which adopts the high-adhesion printing ink described above.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] The invention discloses a high-adhesion printing ink and a printing process thereof. The scheme uses polyurethane as a connecting material, mixes components such as polyurethane emulsion, isopropyl alcohol, and color paste, and stirs them evenly to obtain the printing ink. The printing ink can be adapted to a printing substrate with low surface energy, improves the adhesion performance of the printing ink on the substrate, and the printing ink has relatively excellent water resistance and excellent comprehensive performance.

[0024] In this scheme, the present application first uses octamethylcyclotetrasiloxane, methyltrifluoropropylcyclotrisiloxane and tetramethyltetraenylcyclotetrasiloxane as raw materials, and defines "the mass ratio of the octamethylcyclotetrasiloxane, methyltrifluoropropylcyclotrisiloxane and tetramethyltetraenylcyclotetrasiloxane is 1: (2-2.5): (1-1.2)", and polymerizes to obtain terminal hydroxyl polysiloxane (vinyl fluorinated polysiloxane), and the terminal hydroxyl polysiloxane contains fluorine and vinyl. Then the scheme uses the vinyl group to click with the thiol provided by the thiol to introduce polyhydroxyl groups to obtain a polyol monomer; the polyol monomer participates in the subsequent polyurethane polymerization reaction. On the one hand, the introduction of vinyl fluorinated polysiloxane can improve the hydrophobicity of the polyurethane and reduce the surface tension, thereby improving the adhesion of the ink to the PET substrate; on the other hand, the introduction of polyhydroxyl groups can increase the crosslinking density of the polyurethane, thereby improving the water resistance of the printing ink.

[0025] On this basis, this scheme also introduces 4-methylallyl-1,2-benzenediol, which can provide vinyl and catechol groups. The introduction of catechol groups can effectively improve the adhesion performance of printing inks. At the same time, the scheme uses the click reaction of the vinyl group of 4-methylallyl-1,2-benzenediol with thiol to generate a chain extender. The introduction of the chain extender can also increase the cross-linking density of polyurethane. The scheme compounds the chain extender with a polyol monomer, and the obtained polyurethane emulsion has excellent adhesion to low surface energy printing substrates, and its water resistance is also greatly improved.

[0026] The present application discloses a high-adhesion printing ink and a printing process thereof. The scheme adjusts the formula of the printing ink and optimizes the preparation of the polyurethane connecting material. The printing ink finally obtained has good printing effect and excellent comprehensive performance. It can be widely used in printing on substrates with low surface energy and has high practicality. DETAILED DESCRIPTION

[0027] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] In this embodiment, the preparation steps of 4-methylallyl-1,2-benzenediol are as follows: dissolving catechol in dimethylformamide, adding potassium carbonate and methyl allyl chloride, stirring and reacting at 70° C. for 8 hours, separating and purifying to obtain 2-(oxy-methylallyl)phenol; the molar ratio of the catechol to methyl allyl chloride is 1.3:1; the molar ratio of the catechol to potassium carbonate is 1:0.7.

[0029] 2-(Oxy-methylallyl)phenol was dissolved in N,N-diethylaniline, the temperature was raised to 180°C, the reaction was carried out for 3.5 hours, and 4-methylallyl-1,2-benzenediol was obtained after separation and purification.

[0030] In this embodiment, the molecular weight of polypropylene glycol is 2000; the color paste is Clariant 131-CN.

[0031] Embodiment 1: A method for preparing a high-adhesion printing ink, comprising the following steps:

[0032] Step (1): octamethylcyclotetrasiloxane, methyltrifluoropropylcyclotrisiloxane and tetramethyltetraenylcyclotetrasiloxane are mixed, stirred at 85° C. until uniform, then heated to 100° C., tetramethylammonium hydroxide aqueous solution and deionized water are added, and the mixture is kept warm for 3 h, and the reaction is continued at 140° C. for 2 h, and distilled under reduced pressure to obtain vinyl fluorinated polysiloxane.

[0033] The mass ratio of octamethylcyclotetrasiloxane, methyltrifluoropropylcyclotrisiloxane and tetramethyltetraenylcyclotetrasiloxane is 1:2.2:1.2; the molar concentration of the tetramethylammonium hydroxide aqueous solution is 25%, and the amount used is 0.015wt% of the total mass of the reactants; the amount of deionized water used is 0.08wt% of the total mass of the reactants.

[0034] Step (2): 4-methylallyl-1,2-benzenediol and thiol are mixed, an initiator is added, and the mixture is reacted under ultraviolet light (power is 100 W) for 3 hours to obtain a chain extender; the molar ratio of the thiol to 4-methylallyl-1,2-benzenediol is 1:1.1; the thiol in the chain extender is 2-mercaptoethanol; the initiator is benzoin dimethyl ether, and the amount of the initiator used is 1.5wt% of the total mass of the reactants.

[0035] Vinyl fluorinated polysiloxane and thiol are mixed, an initiator is added, and the mixture is reacted under ultraviolet light (power is 100W) for 3 hours to obtain a polyol monomer; the molar ratio of the vinyl group of the vinyl fluorinated polysiloxane to the thiol group of the thiol is 1:1.2. The thiol in the polyol monomer is 2-mercaptoethanol; the initiator is benzoin dimethyl ether, and the amount of the initiator is 1.5wt% of the total mass of the reactants.

[0036] Step (3): by weight, 25 parts of polypropylene glycol, 4 parts of dihydroxymethyl propionic acid and 7 parts of polyol monomer are mixed, stirred at 80° C. for 30 min, 12 parts of isophorone diisocyanate and 0.5 parts of dibutyltin dilaurate are added, the reaction is kept warm for 1 h, the temperature is lowered to 60° C., 3 parts of 1,4-butanediol and 4 parts of chain extender are added, the reaction is kept warm for 3 h, the temperature is lowered to 50° C., acetone is used to reduce the viscosity, triethylamine is used for neutralization for 30 min, and deionized water is added for dispersion to obtain a polyurethane emulsion with a solid content of 30%.

[0037] Step (4): 60 g of polyurethane emulsion, 10 g of isopropyl alcohol, 10 g of color paste and 30 g of deionized water are mixed and stirred evenly to obtain printing ink.

[0038] Embodiment 2: A method for preparing a high-adhesion printing ink, comprising the following steps:

[0039] Step (1): octamethylcyclotetrasiloxane, methyltrifluoropropylcyclotrisiloxane and tetramethyltetraenylcyclotetrasiloxane are mixed, stirred at 85°C until uniform, then heated to 105°C, tetramethylammonium hydroxide aqueous solution and deionized water are added, and the mixture is kept warm for 2.5 hours, and the reaction is continued at 145°C for 1.5 hours, and distilled under reduced pressure to obtain vinyl fluorinated polysiloxane.

[0040] The mass ratio of octamethylcyclotetrasiloxane, methyltrifluoropropylcyclotrisiloxane and tetramethyltetraenylcyclotetrasiloxane is 1:2.2:1.2; the molar concentration of the tetramethylammonium hydroxide aqueous solution is 25%, and the amount used is 0.015wt% of the total mass of the reactants; the amount of deionized water used is 0.08wt% of the total mass of the reactants.

[0041] Step (2): 4-methylallyl-1,2-benzenediol and thiol are mixed, an initiator is added, and the mixture is reacted under ultraviolet light (power is 100 W) for 2.5 hours to obtain a chain extender; the molar ratio of the thiol to 4-methylallyl-1,2-benzenediol is 1:1.1; the thiol in the chain extender is 3-mercapto-1,2-propylene glycol; the initiator is benzoin dimethyl ether, and the amount of the initiator used is 1.5wt% of the total mass of the reactants.

[0042] Vinyl fluorinated polysiloxane and thiol are mixed, an initiator is added, and the mixture is reacted under ultraviolet light (power is 100W) for 3 hours to obtain a polyol monomer; the molar ratio of the vinyl group of the vinyl fluorinated polysiloxane to the thiol group of the thiol is 1:1.2. The thiol in the polyol monomer is 2-mercaptoethanol; the initiator is benzoin dimethyl ether, and the amount of the initiator is 1.5wt% of the total mass of the reactants.

[0043] Step (3): by weight, 25 parts of polypropylene glycol, 4 parts of dihydroxymethyl propionic acid and 8 parts of polyol monomer are mixed, stirred at 85° C. for 25 min, 12 parts of isophorone diisocyanate and 0.5 parts of dibutyltin dilaurate are added, the reaction is kept warm for 1.5 h, the temperature is lowered to 65° C., 3 parts of 1,4-butanediol and 4 parts of chain extender are added, the reaction is kept warm for 2.5 h, the temperature is lowered to 50° C., acetone is used to reduce the viscosity, triethylamine is used for neutralization for 30 min, and deionized water is added for dispersion to obtain a polyurethane emulsion with a solid content of 30%.

[0044] Step (4): 60 g of polyurethane emulsion, 10 g of isopropyl alcohol, 10 g of color paste and 30 g of deionized water are mixed and stirred evenly to obtain printing ink.

[0045] Embodiment 3: A method for preparing a high-adhesion printing ink, comprising the following steps:

[0046] Step (1): octamethylcyclotetrasiloxane, methyltrifluoropropylcyclotrisiloxane and tetramethyltetraenylcyclotetrasiloxane are mixed, stirred at 85°C until uniform, then heated to 110°C, tetramethylammonium hydroxide aqueous solution and deionized water are added, and the mixture is kept warm for 2 hours, and the reaction is continued at 150°C for 1.5 hours, and distilled under reduced pressure to obtain vinyl fluorinated polysiloxane.

[0047] The mass ratio of octamethylcyclotetrasiloxane, methyltrifluoropropylcyclotrisiloxane and tetramethyltetraenylcyclotetrasiloxane is 1:2.2:1.2; the molar concentration of the tetramethylammonium hydroxide aqueous solution is 25%, and the amount used is 0.015wt% of the total mass of the reactants; the amount of deionized water used is 0.08wt% of the total mass of the reactants.

[0048] Step (2): 4-methylallyl-1,2-benzenediol and thiol are mixed, an initiator is added, and the mixture is reacted under ultraviolet light (power is 100 W) for 3 hours to obtain a chain extender; the molar ratio of the thiol to 4-methylallyl-1,2-benzenediol is 1:1.1; the thiol in the chain extender is 2-mercaptoethanol; the initiator is benzoin dimethyl ether, and the amount of the initiator used is 1.5wt% of the total mass of the reactants.

[0049] Vinyl fluorinated polysiloxane and thiol are mixed, an initiator is added, and the mixture is reacted under ultraviolet light (power is 100W) for 3 hours to obtain a polyol monomer; the molar ratio of the vinyl group of the vinyl fluorinated polysiloxane to the thiol group of the thiol is 1:1.2. The thiol in the polyol monomer is 3-mercapto-1,2-propylene glycol; the initiator is benzoin dimethyl ether, and the amount of the initiator is 1.5wt% of the total mass of the reactants.

[0050] Step (3): by weight, 25 parts of polypropylene glycol, 4 parts of dihydroxymethyl propionic acid and 8 parts of polyol monomer are mixed, stirred at 85° C. for 20 min, 12 parts of isophorone diisocyanate and 0.5 parts of dibutyltin dilaurate are added, the reaction is kept warm for 2 h, the temperature is lowered to 70° C., 3 parts of 1,4-butanediol and 5 parts of chain extender are added, the reaction is kept warm for 2 h, the temperature is lowered to 50° C., acetone is used to reduce the viscosity, triethylamine is used for neutralization for 30 min, and deionized water is added for dispersion to obtain a polyurethane emulsion with a solid content of 30%.

[0051] Step (4): 60 g of polyurethane emulsion, 10 g of isopropyl alcohol, 10 g of color paste and 30 g of deionized water are mixed and stirred evenly to obtain printing ink.

[0052] Comparative Example 1: Example 3 was used as a control experiment. The chain extender prepared in the present application was not introduced into Comparative Example 1, and the other steps remained unchanged.

[0053] A method for preparing a high-adhesion printing ink comprises the following steps:

[0054] Step (1): octamethylcyclotetrasiloxane, methyltrifluoropropylcyclotrisiloxane and tetramethyltetraenylcyclotetrasiloxane are mixed, stirred at 85°C until uniform, then heated to 110°C, tetramethylammonium hydroxide aqueous solution and deionized water are added, and the mixture is kept warm for 2 hours, and the reaction is continued at 150°C for 1.5 hours, and distilled under reduced pressure to obtain vinyl fluorinated polysiloxane.

[0055] The mass ratio of octamethylcyclotetrasiloxane, methyltrifluoropropylcyclotrisiloxane and tetramethyltetraenylcyclotetrasiloxane is 1:2.2:1.2; the molar concentration of the tetramethylammonium hydroxide aqueous solution is 25%, and the amount used is 0.015wt% of the total mass of the reactants; the amount of deionized water used is 0.08wt% of the total mass of the reactants.

[0056] Step (2): Mix the vinyl fluorinated polysiloxane and the thiol, add an initiator, and react under ultraviolet light (power of 100 W) for 3 hours to obtain a polyol monomer; the molar ratio of the vinyl group and the thiol group of the vinyl fluorinated polysiloxane is 1:1.2. The thiol in the polyol monomer is 3-mercapto-1,2-propylene glycol; the initiator is benzoin dimethyl ether, and the amount of the initiator is 1.5wt% of the total mass of the reactants.

[0057] Step (3): by weight, 25 parts of polypropylene glycol, 4 parts of dihydroxymethyl propionic acid and 8 parts of polyol monomer are mixed, stirred at 85° C. for 20 min, 12 parts of isophorone diisocyanate and 0.5 parts of dibutyltin dilaurate are added, the mixture is kept warm for reaction for 2 h, the temperature is lowered to 70° C., 3 parts of 1,4-butanediol are added, the mixture is kept warm for reaction for 2 h, the temperature is lowered to 50° C., acetone is used to reduce the viscosity, triethylamine is used for neutralization for 30 min, deionized water is added for dispersion, and a polyurethane emulsion with a solid content of 30% is obtained.

[0058] Step (4): 60 g of polyurethane emulsion, 10 g of isopropyl alcohol, 10 g of color paste and 30 g of deionized water are mixed and stirred evenly to obtain printing ink.

[0059] Comparative Example 2: Example 3 was used as a control experiment, in which no polyol monomer was introduced into Comparative Example 1, and the other steps remained unchanged.

[0060] A method for preparing a high-adhesion printing ink comprises the following steps:

[0061] Step (1): 4-methylallyl-1,2-benzenediol and thiol are mixed, an initiator is added, and the mixture is reacted under ultraviolet light (power is 100 W) for 3 hours to obtain a chain extender; the molar ratio of the thiol to 4-methylallyl-1,2-benzenediol is 1:1.1; the thiol in the chain extender is 2-mercaptoethanol; the initiator is benzoin dimethyl ether, and the amount of the initiator used is 1.5wt% of the total mass of the reactants.

[0062] Step (2): by weight, 30 parts of polypropylene glycol and 4 parts of dimethylol propionic acid were mixed, stirred at 85° C. for 20 min, 12 parts of isophorone diisocyanate and 0.5 parts of dibutyltin dilaurate were added, the mixture was kept warm for 2 h, the temperature was lowered to 70° C., 3 parts of 1,4-butanediol and 5 parts of a chain extender were added, the mixture was kept warm for 2 h, the temperature was lowered to 50° C., the viscosity was reduced by acetone, triethylamine was neutralized for 30 min, deionized water was added for dispersion, and a polyurethane emulsion with a solid content of 30% was obtained.

[0063] Step (3): 60 g of polyurethane emulsion, 10 g of isopropyl alcohol, 10 g of color paste and 30 g of deionized water are mixed and stirred evenly to obtain printing ink.

[0064] Comparative Example 3: Example 3 was used as a control experiment. In Comparative Example 1, no polyol monomer and chain extender were introduced, and the remaining steps remained unchanged.

[0065] A method for preparing a high-adhesion printing ink comprises the following steps:

[0066] Step (1): by weight, 30 parts of polypropylene glycol and 4 parts of dimethylol propionic acid are mixed, stirred at 85° C. for 20 min, 12 parts of isophorone diisocyanate and 0.5 parts of dibutyltin dilaurate are added, the mixture is kept warm for reaction for 2 h, the temperature is lowered to 70° C., 5 parts of 1,4-butanediol are added, the mixture is kept warm for reaction for 2 h, the temperature is lowered to 50° C., acetone is used to reduce the viscosity, triethylamine is used for neutralization for 30 min, and deionized water is added for dispersion to obtain a polyurethane emulsion with a solid content of 30%.

[0067] Step (2): 60 g of polyurethane emulsion, 10 g of isopropyl alcohol, 10 g of color paste and 30 g of deionized water are mixed and stirred evenly to obtain printing ink.

[0068] Detection experiment:

[0069] 1. Prepare a polyurethane emulsion with a solid content of 30% according to the method disclosed in Examples 1 to 3 and Comparative Examples 1 to 3, spread it evenly on a polytetrafluoroethylene mold, dry it naturally at 25°C for 7 days, and vacuum dry it at 65°C to obtain a polyurethane film sample; cut the polyurethane film sample into 2cm×2cm, weigh it and soak it in deionized water, take it out after soaking for 24 hours, dry the surface moisture and weigh it again, and calculate the water absorption rate.

[0070] 2. Printing ink was prepared according to the method disclosed in Examples 1 to 3 and Comparative Examples 1 to 3, with PET as the substrate, and the adhesion fastness of the ink was determined by the tape method according to the method disclosed in GB / T 13217.7-2009; the water resistance of the printing ink was tested by the following specific steps: after the printing ink was scraped and dried, it was cut into 2 cm × 10 cm strips, half of the strips were immersed in water, and after 24 hours, they were taken out and dried, and rated according to the degree of change of the ink scraping sample and the length of water staining.

[0071] Level 1: The water is severely stained and the scraping sample is severely discolored; Level 2: The water is obviously stained and the scraping sample is obviously discolored; Level 3: The water is slightly stained and the scraping sample is slightly discolored; Level 4: The water is basically not stained and the scraping sample basically does not change color; Level 5: The water is completely colorless and the scraping sample does not change color at all.

[0072] The test data are shown in Table 1.

[0073] Table 1

[0074] project Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Water absorption % 3.87% 3.64% 3.31% 4.43% 6.52% 7.36% Adhesion fastness 100% 100% 100% 97% 96% 92% Water resistance rating Level 5 Level 5 Level 5 Level 4 Level 3 Level 3

[0075] Conclusion: This application discloses a high-adhesion printing ink and its printing process. The scheme adjusts the formula of the printing ink and optimizes the preparation of the polyurethane binder. The printing ink finally obtained has good printing effect and excellent comprehensive performance. It can be widely used in printing on low surface energy substrates and has high practicality.

[0076] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. A method for preparing a high-adhesion printing ink, characterized in that: The following steps are involved: Step (1): octamethylcyclotetrasiloxane, methyltrifluoropropylcyclotrisiloxane and tetramethyltetraenylcyclotetrasiloxane are mixed, stirred at 80-90° C. until uniform, then heated to 100-110° C., tetramethylammonium hydroxide aqueous solution and deionized water are added, and the mixture is kept warm for 2-3 hours, and the reaction is continued at 140-150° C. for 1-2 hours, and distilled under reduced pressure to obtain vinyl fluorine-containing polysiloxane; Step (2): Mix 4-methylallyl-1,2-benzenediol and thiol, add an initiator, and react under ultraviolet light for 2 to 3 hours to obtain a chain extender; Vinyl fluorinated polysiloxane and thiol are mixed, an initiator is added, and the mixture is reacted under ultraviolet light for 2 to 3 hours to obtain a polyol monomer; Step (3): polypropylene glycol, dimethylol propionic acid and polyol monomer are mixed, stirred at 80-85° C. for 20-30 min, isophorone diisocyanate and dibutyltin dilaurate are added, the reaction is kept warm for 1-2 h, the temperature is lowered to 60-70° C., 1,4-butanediol and a chain extender are added, the reaction is kept warm for 2-3 h, the temperature is lowered to 40-50° C., acetone is used to reduce the viscosity, triethylamine is used for neutralization for 20-30 min, and deionized water is added for dispersion to obtain a polyurethane emulsion; Step (4): mixing the polyurethane emulsion, isopropyl alcohol, color paste and deionized water, stirring evenly to obtain printing ink; In step (2), the preparation steps of 4-methylallyl-1,2-benzenediol are: Dissolve catechol in dimethylformamide, add potassium carbonate and methyl chloropropene, stir and react at 65-75°C for 8-10 hours, separate and purify to obtain 2-(oxy-methylallyl)phenol; dissolve 2-(oxy-methylallyl)phenol in N,N-diethylaniline, heat to 180-190°C, react for 3-4 hours, separate and purify to obtain 4-methylallyl-1,2-benzenediol; In step (2), the thiol is 2-mercaptoethanol and / or 3-mercapto-1,2-propylene glycol; the molar ratio of the thiol to 4-methylallyl-1,2-benzenediol is 1:(1-1.1); and the molar ratio of the vinyl group of the vinyl fluorinated polysiloxane to the thiol group of the thiol is 1:(1-1.2).

2. The method for preparing a high-adhesion printing ink according to claim 1, characterized in that: In step (2), the amount of the initiator is 1-1.5 wt% of the total mass of the reactants; the initiator is any one of benzoin ethyl ether, benzoin dimethyl ether, and 1-hydroxycyclohexyl phenyl ketone.

3. The method for preparing a high-adhesion printing ink according to claim 1, characterized in that: In step (1), the mass ratio of octamethylcyclotetrasiloxane, methyltrifluoropropylcyclotrisiloxane and tetramethyltetraenylcyclotetrasiloxane is 1:(2-2.5):(1-1.2); the amount of the tetramethylammonium hydroxide aqueous solution is 0.01-0.015wt% of the total mass of the reactants; and the amount of deionized water is 0.05-0.08wt% of the total mass of the reactants.

4. The method for preparing a high-adhesion printing ink according to claim 1, characterized in that: The molar ratio of catechol to methyl chloropropene is (1.2-1.5):1; the molar ratio of catechol to potassium carbonate is 1:(0.6-0.7).

5. The method for preparing a high-adhesion printing ink according to claim 1, characterized in that: In step (3), the amounts of the components used, in parts by mass, include: 25-30 parts of polypropylene glycol, 2-4 parts of dimethylol propionic acid, 6-8 parts of polyol monomer, 10-15 parts of isophorone diisocyanate, 0.3-0.5 parts of dibutyltin dilaurate, 2-4 parts of 1,4-butanediol, and 3-5 parts of chain extender; the solid content of the polyurethane emulsion is 30-40%.

6. The method for preparing a high-adhesion printing ink according to claim 1, characterized in that: In step (4), the mass ratio of the polyurethane emulsion, isopropyl alcohol, color paste and deionized water is 6:1:1:

3.

7. A high-adhesion printing ink prepared according to the preparation method according to any one of claims 1 to 6.

8. An ink printing process, characterized in that: A high adhesion printing ink as described in claim 7 is used.

Citation Information

Patent Citations

  • Preparation method of intrinsic in-situ self-repairing anti-corrosion polymer

    CN115477734A

  • High-strength steel strand and lifting point applied by same

    CN115506224A

  • High-adhesiveness water-based printing ink and preparation method thereof

    CN115746622A

  • Antibacterial cotton fiber blended yarn and preparation method thereof

    CN118147799A